2015
DOI: 10.1039/c5ra06945a
|View full text |Cite
|
Sign up to set email alerts
|

Lead biotransformation potential of allochthonous Bacillus sp. SKK11 with sesame oil cake extract in mine soil

Abstract: The potential of allochthonous Bacillus sp. SKK11 and sesame oil cake extract for the immobilization of Pb in mine soil was investigated in this study. The isolate SKK11, isolated from a brackish environment and identified as Bacillus sp. based on partial 16S rDNA sequencing, exhibited maximum resistance to Pb (750 mg L À1 ). Growth kinetic studies revealed that the presence of oil cake extract (2%) increased the biomass of the isolate SKK11. Transmission electron microscopy and X-ray diffraction studies showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A minor difference in the growth response was observed according to the metal. The differences in the growth profile could be associated with the toxicity and bioavailability of metals (Govarthanan et al 2015a).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minor difference in the growth response was observed according to the metal. The differences in the growth profile could be associated with the toxicity and bioavailability of metals (Govarthanan et al 2015a).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Several physical, chemical, and biological methods have been proposed for the removal of heavy metals from contaminated soil and water (Shi et al 2009), of which bacteria-based bioremediation is considered as a promising and viable method. Bacteria-based bioremediation is less expensive and eco-friendly (Govarthanan et al 2015a), but is highly influenced by several factors, such as survival of bacteria in contaminated soil or water, influence of abiotic factors on the growth of bacteria, mechanism of metal detoxification, expression rate of metal detoxificiation genes, and influence of pollutants on bacterial activity (Suja et al 2014; Govarthanan et al 2015b; Praburaman et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Bacillus sp. SKK11 produce PbS crystals when cultured in LB medium ( 1 = 4 strength) supplemented with Pb(NO 3 ) 2 (Govarthanan et al 2015). Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…The rich nutrients present in the SM had extended the log phase of growth kinetics. Our previous studies reported the nutrient properties of oil cakes and the growth profile of microorganisms [5][6][7]. The growth kinetics showed that the SM could be used as an alternative to the synthetic medium for the cultivation of bacteria.…”
Section: Growth Kinetics Of Rahnella Sp Rmmentioning
confidence: 99%
“…However, the disadvantages and ineffectiveness of these methods have been widely reported [2][3][4]. An alternative to the application of phyisco-chemical methods in heavy metal removal from contaminated soil/water is the use of microorganisms, capable of reduce, immobilize, transform, and leach the metal(loid)s [5][6][7].…”
Section: Introductionmentioning
confidence: 99%